Persepsi Mahasiswa terhadap Sistem Manajemen Pembelajaran Online di Universitas Advent Indonesia - Albinur Limbong (TeIKa, 2022)
This paper is a study of students’ perception onto UNAI online system. The data for students’ perception is obtained from questioners filled through online by students. The objective of the study is to see how well UNAI online system perceived by students. The study was conducted during the odd semester 2021/2022. The population was 1636 students, and samples taken randomly was 105 students. The questioner consists of 6 parameters of perception: benefit of online system, usage simplicity, friend support, facility completeness, usage interest, dan usage frequency. The study shows that based on individual regression analysis, the benefit, simplicity, friend support, facility completeness significantly have a significant effect on interest to use the online system, and the interest to use the online system has an effect on usage frequency. However, on simultaneously regression analysis among the four parameters, only two parameters (the perception of benefits and facility completeness) have a significant effect on students’ interest using the online system. Based on cross tabulation analysis, faculty of education students have better perception on UNAI online system compared to other faculty students, senior students have better perception compared to other batches, and female students have better perception than male students. The findings of the study imply that the facility of online system, in terms of network, bandwidth, computer facility, and learning resources need to be accomplished in order to improve the students’ academic achievement during the online learning era due to covid-19 pandemic.